SOLUBLE ENDOGLIN AS AN EARLY PREDICTION MARKER OF INTRAUTERINE GROWTH RETARDATION - Gromova, A.M.; Berezhna, V.A.; Gromova, O.L.; Lyakhovska, T.Y.; Ketova, O.M. (World of Medicine and Biology, 2021)
High levels of circulating endoglin contribute to the development of endothelial dysfunction, which underlies the pathogenesis of intrauterine growth retardation and can be used as a prognostic marker for the development of this pathology. We collected serum from pregnant women with intrauterine growth retardation (n-41) initially at diagnosis and before delivery, and pregnant women with physiological pregnancy (n-8), using enzyme-linked immunosorbent assay to test soluble endoglin levels. It was found that the level of soluble endoglin concentration was 7.2±0.2 at the initial examination and 9.5±0.1 at the repeated examination in women who gave birth to low birth weight children with fetal developmental delay and constitutionally small children, while the level of this factor in women in the comparison group was 3.7±0.3. It was found that the level of soluble endoglin concentration was significantly higher in women who gave birth to children with intrauterine growth retardation than the level of this factor in women in the comparison group, which is highly informative to use its prognostic value.